The Study & Analysis of Oscillation Changes of Discharge & Precipitation in Mund Basin - dr.gholam hassan jafari; mahdi doostkamiyan (جغرافیا و آمایش شهری منطقه‌ای, 2016)
The aim of this study was to study the changes & Detection of discharge & precipitation circles & annual precipitation of Mund basin. For this purpose, the annual discharge and precipitation data of this basin were extracted for the stations of  Baba arab, dehram, dehrud, dejgan, hakan, karzin strait,Tangab & Hanifaghan srations during 1976-2011, then was scrutinized and analyzed  by the  use of trend  and harmonic analysis methods  in MATLAB software environment . The results showed that a 2-6 short time circle has been dominant  on discharge & precipitation of Mund basin. Nevertheless, some long term cycles such as 17 & 25 year have been observed in the discharge of this river. The results of the analysis process of discharge & precipitation showed that the decrease & increase of river discharge was affected by the decrease & increase of basin precipitation in most of the stations. Nevertheless it can’t be deducted definitely that discharge circles & changes  of Mund basin was dependant  on precipitation. Hence the effects of morphologic & geomorphologic factors of this basin can’t be disregarded.